Kinetic study of monascus purpureus in solid-state fermentation for red pigment production - Said, Farhan Mohd; Abdul Munaim, Mimi Sakinah; Abdul Rasid, Ruwaida; Mat Yasin, N. H. (2019)
Red pigment produced by Monascus species is known as an edible pigment, rich in wide range of biological activities. The aim of this research is to study the kinetic characterization of red pigment production throughout the solid state fermentation. Factors such as nutritional factors (nitrogen source and carbon source) and environmental factors (moisture content, pH, inoculum size) on red pigment were investigated. The results indicated that the highest maximum growth rate (µmax), mean cell (Pcells) conversion of substrate into biomass (Yx/s), conversion of substrate into red pigments (Yp/s) and conversion biomass into red pigments (YP/X) were obtained at day 5 of fermentation period at 2% peptone. Where, the values were 0.1182 day-1, 119.7g ml-1 day-1, 92.53g g-1, 1.35g g-1 and 0.016g g-1, respectively. The results also indicated that the conversion of biomass to red pigment is improved with higher peptone concentration. Overall, the finding concluded that the red pigment produced by Monascus purpureus FTC 5357 in solid state fermentation produced the highest pigment at 2% peptone, 5g of oil palm fronds, pH 6, 50% of moisture content, at 30oC and 108 spores ml−1 inoculum size. These findings are important knowledge to be used for optimizing the red pigment production.